Wind analysis for wind power : Part I - THOMAS, S. I. T. (MAUSAM, 1981)
Utilisation of energy from the winds has assumed significant importance in the context of the energy crisis which is one of the challenging problems facing the world today. In India there is much scope for making use of the wind power. In planning the locations, the type and design of the most suitable types of wind mills information on winds at the desired locations is very valuable. In this paper, the author has made a frequency analysis of hourly values of winds from the records of the Dines Pressure Tube Anemograph at Ahmedabad during the five year period 1973-77. The frequency distribution of hourly values of winds in the four ranges 0-9 kmph, 10-14 kmph, 15-19 kmph and 20 kmph and above 4as been determined. Monthwise frequency distribution is also presented.